Sustainable Tourism: Policy Directions - Tania, Theresia Levi; Sinambela, Ella Anastasya (Metromedia, 2022)
Sustainable tourism aims to establish an appropriate balance between the environmental, economic and socio-cultural aspects of tourism development and play an important role in conserving biodiversity. It tries to minimize its impact on the local environment and culture so that it will be available to future generations, while contributing to income generation, employment and conservation of local ecosystems. In the national context, sustainable tourism in Indonesia develops in harmony with global dynamics. Therefore, a policy direction is needed. This paper is a brief study of sustainable tourism and policy directions.